Internet and Social Media Impact on Health and COVID-19 in Puerto Rico - Ivan De la Cruz (Athens Journal of Health and Medical Sciences)
This paper analyzes the impact of social media and Internet in relation to health and COVID-19 in Puerto Ricans from the Information Society perspective, including the impact on patient-to-doctor relationship and health services demand, impact on patient-to-patient relationship, knowledge and understanding of information and Internet impact factors in relation to health. An online survey of 124 cases confirmed its effects on the doctor and patients.